(untitled) (Asian Journal of Social Science Studies, 2022)
COVID-19 broke out in the earth in 2020, economic and social development of the Macao SAR has brought huge economic losses and inestimable impact on the tourism service industry. This research focuses on the tourism service industry in the Macao SAR, study the economic trend and impact of the COVID-19 on the tourism service industry. Analyze the impact of the enterprise from the four aspects of the enterprise’s production and operation, the use of funds, the sales method and the company’s management, research put forward the difficulties and problems encountered by the tourism service industry enterprises. The study provides feasible recommendations and measures for the tourism service industry to address the impact of the COVID-19 and restore economic development.